Circuit-free, optoelectronic sensing of electrodermal activities based on photon recycling of a micro-LED - Ding, He; Lv, Guoqing; Shi, Zhao; Cheng, Dali; Huang, Yunxiang; Yin, Lan; Yang, Jian; Wang, YongTian; Sheng, Xing (bioRxiv, 2020)
Conventional epidermal electronics integrate multiple power harvesting, signal amplification and data transmission components for wireless biophysical and biochemical signal detection. This paper reports the real-time electrodermal activities can be optically captured using a microscale light-emitting diode (micro-LED), eliminating the need for complicated sensing circuit. Owing to its strong photon-recycling effects, the micro-LED's photoluminescence (PL) emission exhibits a superlinear dependence on the external resistance. Taking advantage of this unique mechanism, the galvanic skin response (GSR) of a human subject is optically monitored, and it demonstrates that such an optoelectronic sensing technique outperforms a traditional tethered, electrically based GSR sensing circuit, in terms of its footprint, accuracy and sensitivity. This presented optoelectronic sensing approach could establish promising routes to advanced biological sensors. Competing Interest Statement The authors have declared no competing interest.